Applying the CAPM Model in Identifying the Electricity Retail Price in Ho Chi Minh City, Vietnam - Ha, Nguyen Minh; Hoang, Nguyen Duy (International Journal of Energy Economics and Policy, 2017)
This paper applies the Capital Asset Pricing Model (CAPM) model to calculate the expected return rate equivalent to electricity retail price in Ho Chi Minh City, with observed 1,464 hours of Ho Chi Minh city Power Corporation. The study suggests the model of calculate the electricity retail price so that government has more tools to adjust the electricity prices in electricity market, and recommends an electricity retail price list of 12 levels, with the minimum sale price of 965VND/kWh and maximum sale price of 1,675VND/kWh. Specifically, with current electricity sale price of 1,447VND/kWh, the Ho Chi Minh city Power Corporation reaches the highest return rate of 11.7% and the return rate fluctuates from -12% to 11.7% (price of 1,447VND/kWh with rf=6%). The sensitive analysis shows that from rf=12% above, the return rate always reaches the maximum point at price of 1,313VND/kWh (It is an average cost to produce 1kWh). Keywords: CAPM; Electricity retail price; Electricity market. JEL Classifications: Q4